The effects of thiamine supplementation on patients with heart failure: A systematic review and meta-analysis of randomized controlled trials - Mengqi Xu; Jianlin Ji; Qunfeng Lu; Jinghuan Gong; Zhenlan Luo; Lingyan Zhu (Elsevier, 2022)
Background: Micronutrients can benefit patients with heart failure (HF). Thiamine is a critical vitamin, while the impact of thiamine supplementation on patients with HF remains unclear. Systematic review and meta-analysis were conducted to evaluate the effects of thiamine supplementation on clinical outcomes in patients with HF. Methods: Databases including Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, Embase, Scopus, and CNKI were searched from inception to June 29th 2022. Randomized controlled trials (RCTs) comparing thiamine supplementation with placebo were included. Meta-analysis was conducted with the software Review Manager 5.4. The quality assessment was performed according to Cochrane Risk of Bias Tool 2.0. Results: Eight studies including 384 patients were included in this review. The results of overall systematic review showed no benefit of thiamine supplementation in HF patients. Compared with the control group, the experimental group had no statistically significant improvements in LVEF (Mean Difference, − 0.19; 95 % CI, − 2.78 to 0.96; I2 = 49 %; P = 0.10) in patients with chronic heart failure (CHF). Other outcomes including NYHA class, BNP or NT-proBNP, thiamine status, symptom changes, and quality of life were not improved by thiamine supplementation in CHF patients. Similarly, no improvements in clinical outcomes were found in patients with acute heart failure (AHF) in the studies included. Conclusions: This systematic review and meta-analysis found no evidence to support the effects of thiamine supplementation in patients with HF, though thiamine supplementation is promising in improving cardiac functions, thiamine status and relieving HF-related symptoms. More well-designed RCTs with large sample sizes are required.